Using Wikis to teach History Education to 21st Century Learners: A Hermeneutic perspective - Sebbowa, Dorothy; Ng'ambi, Dick; Brown, Cheryl (Critical Studies in Teaching and Learning, 2023)
This paper argues that history education is becoming dangerously obsolete, as it does not always relate to the contemporary needs of 21st century learners, who often find history useless and irrelevant to their present situation. This challenge is attributed to, among other reasons, the way history is taught through largely lecture-driven pedagogies that significantly reduced active learner engagement. This article draws on Gadamer’s Hermeneutic philosophy to advocate for dialogue in understanding and interpreting history artifacts using 21st century technologies. Gadamerian Hermeneutics focuses on horizons of understanding through open-ended questioning and answering between past and present rather than transmission to passive audiences. The article argues for the collaborative interpretation of history meanings between teachers and students mediated by a Wiki. The methodology involved a case study of pre-service teachers enrolled at Makerere University in Uganda. The purely qualitative study draws on Gilly Salmon’s five-stage model of online learning. The findings indicate that participants successfully engaged with the first three stages - access and motivation, online socialisation, and information exchange - but less so with stages four and five, knowledge construction and development. The paper concludes by proposing a framework that could be useful to teachers wanting to facilitate history education using modern approaches that are relevant and meaningful to today’s learners.